2021
DOI: 10.22541/au.161893580.04167261/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the environmental factors related to the decrease in Pediatric Emergency Department referrals for acute asthma during the SARS-CoV-2 pandemic

Abstract: Background: Asthma exacerbations, a common reason for Pediatric Emergency Department (PED) referral, can be triggered by multiple factors, including infections, air pollution and allergens. Lockdown measures and other public health interventions during the SARS-CoV-2 pandemic determined radical changes to behavioral and social habits, that were reflected by a reduction in the transmission of all respiratory pathogens and in the emissions of relevant air pollution anthropogenic sources. Objective: This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, when the restrictions were lifted, there were increased visits during the fall but SO 2 levels remained low, raising the possibility for other driving factors [49]. In Europe, there was an observed decline both pollutant levels and ED visits [50,53] and hospitalizations due asthma exacerbations [54]. Conversely, Sayed et al [55] reported a reduction in pediatric asthma-related healthcare visits but not observe changes in air pollutant levels of PM 2.5 , PM 10 , O 3 and NO 2 during that time period when compared with previous historic trends.…”
Section: Impact Of Coronavirus Disease 2019mentioning
confidence: 99%
“…However, when the restrictions were lifted, there were increased visits during the fall but SO 2 levels remained low, raising the possibility for other driving factors [49]. In Europe, there was an observed decline both pollutant levels and ED visits [50,53] and hospitalizations due asthma exacerbations [54]. Conversely, Sayed et al [55] reported a reduction in pediatric asthma-related healthcare visits but not observe changes in air pollutant levels of PM 2.5 , PM 10 , O 3 and NO 2 during that time period when compared with previous historic trends.…”
Section: Impact Of Coronavirus Disease 2019mentioning
confidence: 99%
“…Although there were detrimental effects on children and young people's physical and mental well-being during the pandemic, some studies reported improvements in seasonal respiratory allergy symptom control, particularly during lockdown measures. 52,53 Nonpharmaceutical interventions, such as handwashing, masks, and social/physical distancing, reduction in the concentrations of traffic-related air pollutants 54,55 and decline in other respiratory infections incidence, may have contributed to reduced impact on allergic disease 56,57 particularly respiratory, [58][59][60][61][62][63] number of exacerbations 59,62,[64][65][66][67][68][69][70][71] and the odds of emergency room visit and/ or hospital admissions. 59,66,[72][73][74][75][76][77][78] Improvements were normally associated with time spent at home, and stronger effects were found in some studies among individuals with severe disease.…”
Section: Are There Any Known Benefits and Harms Of Lockdown Measures ...mentioning
confidence: 99%